Coating Lithium Titanate with Nitrogen-Doped Carbon by Simple Refluxing for High-Power Lithium-Ion Batteries - Du Hoang Long; Jeong, Min-Gi; Lee, Yoon-Sung; Choi, Wonchang; Lee, Joong Kee; Oh, In-Hwan; Jung, Hun-Gi (American Chemical Society, 2015)
Nitrogen-doped carbon is coated on lithium titanate (Li4Ti5O12, LTO) via a simple chemical refluxing process, using ethylenediamine (EDA) as the carbon and nitrogen source. The process incorporates a carbon coating doped with a relatively high amount of nitrogen to form a conducting network on the LTO matrix. The introduction of N dopants in the carbon matrix leads to a higher density of C vacancies, resulting in improved lithium-ion diffusion. The uniform coating of nitrogen-doped carbon on Li4Ti5O12 (CN-LTO) enhances the electronic conductivity of a CN-LTO electrode and the corresponding electrochemical properties of the cell employing the electrode. The results of our study demonstrate that the CN-LTO anode exhibits higher rate capability and cycling performance over 100 cycles. From the electrochemical tests performed, the specific capacity of CN-LTO electrode at higher rates of 20 and 50 C are found to be 140.7 and 82.3 mAh g(-1)., respectively. In addition, the CN-Li4Ti5O12 anode attained higher capacity retention of 100% at 1 C rate after 100 cycles and 92.9% at 10 C rate after 300 cycles.
Keywords: ELECTROCHEMICAL PERFORMANCE; TITANIUM NITRIDE; COATED LI4TI5O12; FACILE SYNTHESIS; ANODE MATERIAL; SPINEL; CHEMISTRY; ELECTRODE; SURFACE